Analytical Study in Common Sociology Motifs in the Cartoon Works of Hadi Heidari - poorheshmati, Hamed (LANGUAGE ART, 2022)
Some of the ideas and events serve a prominent position in human life, as though they lead humans to insistence and repetition by becoming a part of the concerns. Ultimately, they have emerged as personally permanent characteristics in humans' conscious and unconscious imagery. But, constant iterations of the mentioned imagery represent subjects that no information about its reality is available under normal circumstances. Notwithstanding, repetition is a linguistic-criticism phenomenon, sometimes it is offered as a motif appearing in the context of essential elements within a poem's text, signs and implications in which the poet uses codes and poetic images among them in order to add beauty and attraction to his/her text. Cartoon Art, as a picture, exaggerated and ridiculous traits offer outstanding design of people or objects and, using an analogy or a metaphor for a plan that sometimes combines with recurring elements and laughs along with the audience, the thoughts and feelings affect his. Thus, this study aims to examine cartoon images Hadi Heidari, the function is studded motif in his works uncover. Methods this cross-sectional study that deals with the depiction of certain objects to reveal the secrets that can mingle with forms of visual elements in his work to understand. Ultimately, they have emerged as personally permanent characteristics in humans' conscious and unconscious imagery.